Connected cows and cyber chickens? Stocktaking and case studies of digital livestock tools in Kenya and India. (February 2022) - Daum, Thomas; Ravichandran, Thanammal; Kariuki, Juliet; Chagunda, Mizeck; Birner, Regina
Abstract: CONTEXT: There are high hopes that digital tools can reduce constraints to livestock development, which in turn promises to alleviate poverty, improve food and nutrition security, and reduce environmental footprints. Yet, little systematic evidence exists on the state of digital livestock in low- and middle-income-countries. Thus, it remains unclear whether such high hopes are justified. OBJECTIVE: Focusing on India and Kenya, we aim to better understand, among others, the degree of technological sophistication of the digital tools used, the types of value chains and constraints addressed, the types of business models pursued, and more broadly the opportunities and challenges of digital tools for agricultural development. METHOD: We combine a review of digital tools in India and Kenya with three "on-the-ground" case studies: Herdman, a tool for Indian dairy organizations working with small-scale livestock keepers, facilitating data collection and supervision of field agents; Farmtree, a tool supporting medium-scale livestock keepers in India to manage their herds, and iCow, an e-extension tool for farmers in Kenya. For the review, we develop a conceptual framework that distinguishes different types of tools: 1) "simple digital tools", providing generic information, 2) "smart digital tools", providing tailored information based on data entered by livestock keepers, 3) "smart digital tools", using data from sensors, 4) "digital tools for value chains", enabling the integration of value chain actors, 5) "automated digital systems", which are coupled with robots, allowing for automation. RESULTS AND CONCLUSIONS: Digital tools provide many new options to address constraints to livestock development. So far, most tools are "simple digital tools", followed by "smart digital tools" using manual data and tools for value chains. Such tools that only require smartphone ownership are the "sweet spot" for supporting digital livestock development; however, even embodied "smart digital tools" using sensors can be of relevance for small-scale livestock keepers with appropriate organizational models. Most digital tools focus on dairy production, suggesting neglect of other types of livestock, and there are few tools for pastoralists. SIGNIFICANCE: The conceptual framework as well as many of the lessons learned are of relevance to understanding the contribution of digital tools to livestock development - and agricultural development more broadly - in low- and middle-income-countries. While digital tools are no silver bullets – and come with some new challenges such as data security and sovereignty concerns - they are likely to become a key pillar of agricultural and livestock development in the near future. Graphical abstract: Unlabelled Image Highlights: There are high hopes but little evidence concerning the potential of digital agriculture, i.e. regarding livestock We take stock of digital livestock tools in India and Kenya and present three "one-the-ground" case studies Digital tools provide new options for livestock development, i.e. "smart" tools providing tailored advice using farm data Concerns arise on data sovereignty, digital divide, and changing power relations, calling for governance solutions. Digital tools are no silver bullets but will become key pillars of agricultural and livestock development